RE-EXAMINATION OF YUSHKINITE: CHEMICAL COMPOSITION, OPTICAL PROPERTIES AND INTERLAYER CHARGE TRANSFER - Moëlo Y.; Cario L.; Rouer O.; Cervelle B. (My University, 1999)
The hydroxy-sulphide yushkinite from the type deposit has been re-examined by electron probe microanalysis and reflectance measurement. The EPMA indicates minor Cu (up to 1.5 wt.%) and confirms an excess of V. Taking into account its composite structure (brucite-like hydroxide layer alternating with a berndtite-type sulphide layer) the proposed structural formula is, with the addition of minor intercalated Cu: [(Mg0.71Al0.36V0.03) Σ1.10(OH)2.18O0.02]Cu0.02 [VS2]. At the crystal scale, some crystal edges give a variable excess of Si and Al (in the 1/1 ratio), indicating a late topotactic intergrowth with a layered alumino-silicate (or a composite silicate-sulphide). New specular reflectance data are given in air and oil from 400 to 800 nm, with the polarization plane parallel or perpendicular to the elongation. The refractive index n and absorption coefficient k are given; no absorption band exists in the perpendicular position, with constant n close to 1.9, and k to 0.3. In a parallel position, a pseudo-transparency window is centred around 500-520 nm (~2.4 eV). The main absorption band, centred around 730 nm (~1.7 eV), corresponds probably to a transition t2g→ eg related to intra-layer V-V bonding. Charge transfer from the brucite-type layer to the VS2 one, strictly controlled through H-bonding, induces a mean formal valency of V close to 3.6. Yushkinite is compared with other synthetic layered hydroxy-sulphides, as well as brucite-type intercalated compounds.